Essays on monetary policy with sterilised intervention in emerging market economies - Devadas, Sharmila (2013)
The purpose of this thesis is to provide a new simple theoretical framework for understanding the sterilisation of foreign exchange intervention within a monetary policy framework where a short-term interest rate is the main policy instrument. Another aim is to carry out new empirical analysis that compares and contrasts the effects of intervention on base money growth with its effects on broad money growth, and to investigate if these effects are associated with common country characteristics in terms of the nature of intervention, balance of payments flows and monetary policy frameworks.